Globalization and the world of large cities - Lo, Fu-chen; Lo, Fu-chen.; Yeung, Yue-man. (Tokyo ; New York : United Nations University Press, 1998)
In this volume, the world's urban future is analyzed through a number of critical themes that relate to globalization, such as urban corridors, Islamic cities, new technologies, transport and telecommunications, financial centres, and food issues.
Part 1 Regional surveys and selected world cities -- Part 2 Key issues about the urban future.
Includes bibliographical references and index.
Keywords: International economic relations; Metropolitan areas; Urbanization